The subgenus Eurysunius Reitter in Turkey, with the description of three new species (Coleoptera: Staphylinidae: Astenus). Issue 1 (2nd January 2022) - Anlaş, Sinan
Abstract : Three new species of Astenus ( Eurysunius ) Dejean are described from Turkey: A. sundikenicus sp. n. (Eskişehir), A. turkmendagicus sp. n. (Eskişehir-Kütahya border), and A. mekeensis sp. n. (Konya). Additional records of seven species of Eurysunius as well as a checklist of the members of the genus is provided. The distribution of 25 species known in Turkey is mapped. http://www.zoobank.org/urn:lsid:zoobank.org:pub:BD42FD95-31A1-4061-8B7E-75CB036E71BB